Growth enhancement of Anthurium seedlings using Arbolina - João Victor Barbosa Silva; Ana Cecília Ribeiro Castro; Carlos Alberto Kenji Taniguchi; Fabiana Rodrigues da Silva; Natália Florêncio Martins; Júlio César DoVale (Ornamental Horticulture)
Species of the Anthurium genus are renowned for their ornamental and landscaping potential. Among native Brazilian species, Anthurium affine and Anthurium maricense are particularly suited for indoor cultivation due to their shaded-condition tolerance and slow growth. However, accelerating the production cycle presents a significant challenge for producers. Organic carbon nanoparticle-based biostimulants, such as Carbon Dots, have shown promise by enhancing nutrient uptake, water use efficiency, and plant growth. This study evaluated the effects of a biostimulant nanocomposite (Arbolina®) based on organic carbon nanoparticles on seedlings of A. affine and A. maricense. Seedlings (85 days old) were transplanted and treated with the biostimulant at 60 mg L-1 concentration via foliar and soil applications, alongside a control group. Biostimulant treatments were applied biweekly for a total of four applications. Plant height and leaf count were measured every 30 days, while fresh weight, leaf area, root volume, and dry weights of leaves and roots were assessed after 96 days of cultivation. Results showed no significant variations in aerial growth parameters; however, soil application significantly increased root volume in both species. In A. affine, differences in root volume were also detected under foliar application. It is concluded that the biostimulant, at the applied concentration, did not accelerate the shoot growth of juvenile seedlings within the experimental period. Nonetheless, soil application was identified as the most effective method for promoting root system development. These findings demonstrate the potential for targeted use of biostimulants to optimize specific growth traits in Anthurium cultivation.